Kanji Ability Mastery of Japanese Literature Study Program’s Students, Faculty of Arts, Udayana University - I Gede Oeinada (Udayana Journal of Social Sciences and Humanities, 2018)
Kanji ability of Japanese Department students, Faculty of Arts, Udayana University namely the third-year students and the second-year students is measured by a test on Kanji mastery. This test measures 12 aspects of Kanji mastery ranging from the mastery of meaning, word structure, form, writing, to how to read Kanji’s onyomi. The third-year students have stopped receiving Kanji lecture while the second-year students are still getting Kanji lecture. The test results indicate that there is a relevancy between Kanji lecture and the average ability increasing in Kanji mastery aspects of the students. The increasing on the scale value of the test results by the third-year students is only on 3 aspects i.e. only 25% of the total Kanji mastery aspects. Meanwhile, in the second-year students is as much as 7 aspects i.e. 58% of the total Kanji mastery aspects measured. The weak aspect of Kanji mastery that needed to be increased in both classes is the aspect of how to read the Kanji’s onyomi. This aspect can be trained by utilizing the communication and information technology (CIT) of Japanese language learning that has been available online namely the Kanji-en site. The Kanji-en site has Kanji exercises that emphasize the aspect of Kanji onyomi reading so that it is suitable to be used in improving the Kanji ability of Japanese Department students, Faculty of Arts, Udayana University. By using an interactive learning media that is available in this site, surely it can increase the motivation and spirit of Japanese language learners, especially in the field of Kanji mastery.